52*67-27*3=

Simple and best practice solution for 52*67-27*3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52*67-27*3= equation:


Simplifying
52 * 67 + -27 * 3 = 0

Multiply 52 * 67
3484 + -27 * 3 = 0

Multiply -27 * 3
3484 + -81 = 0

Combine like terms: 3484 + -81 = 3403
3403 = 0

Solving
3403 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x+110=6x+92 | | 0.5x(x-3)=(x-3)(1.5x-1) | | (x-y)^1/4 | | 3x^2(4x^2-5x+3)= | | 7x^2-125=2500 | | 6y+6=7y | | 7n-1=4n+1 | | 2a/(b^2-4ac)^1/2 | | -63=-9 | | 5y-5+y+41=8+7y+32+3y | | 12=384/q | | 12y+2x=138 | | 6s+2s=6 | | 60=4(2x-5) | | ((7x^4/(x^2-25))/((x^6)/(x-5)^2)) | | 16=x(3+x) | | 36=2x^2+x | | 8x+2(1.5x)=80 | | 20=x-6 | | (5y-3x)/3=x-y | | 45=23+x | | 40=9/5c | | Y=7Sin(6x+5)+2Cos(3x-2) | | 5x-(-2x+1)=2 | | 2x+6+x+1=3(x-1)+6 | | 3x^2-8y^2=-5 | | 2/10➗3/100 | | 0=-18v^2+1476v-26600 | | 3(x-3)+4=2[-(x-5)-4(2x+1)] | | 4a^2+4a=-15 | | 4a^2+4=-15 | | 2x^1-1=0 |

Equations solver categories